2020
DOI: 10.18502/ijml.v7i4.4802
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Aqueous Extract of Boswellia Serrata on Memory Impairment Induced by Lipopolysaccharide

Abstract: Background and Aims: The therapeutic effects of the olibanum, the resin of Boswellia serrata (B. serrata) from the Burseraceae family in inflammatory disease have been reported. There are more than 200 active ingredients in this resin, including Boswellic acid. It is proposed that aqueous extract of B. serrata can improve memory impairment induced by cerebral inflammation result in the administration of lipopolysaccharide (LPS). Materials and Methods: In this study, after the treatment of rats with LPS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It works by inhibiting inflammation and oxidative stress. It may modulate the activity of multiple molecular targets that influence the signaling pathways that contribute to the pathogenesis of cognitive impairment (Borooni et al 2020 ; Marefati et al 2020 , 2021 , 2022 ). Mohammed et al (2022) observed that BA modulated the expression of parameters related to the Wnt/-catenin pathway and decreased the expression of TNF-α IL-1β, attenuated lipid peroxidation, and raised total brain antioxidants.…”
Section: Resultsmentioning
confidence: 99%
“…It works by inhibiting inflammation and oxidative stress. It may modulate the activity of multiple molecular targets that influence the signaling pathways that contribute to the pathogenesis of cognitive impairment (Borooni et al 2020 ; Marefati et al 2020 , 2021 , 2022 ). Mohammed et al (2022) observed that BA modulated the expression of parameters related to the Wnt/-catenin pathway and decreased the expression of TNF-α IL-1β, attenuated lipid peroxidation, and raised total brain antioxidants.…”
Section: Resultsmentioning
confidence: 99%
“…Spinosa seeds exhibited significant anti-depressant-like effects by increasing the mobility time and total distance in the force swimming and open field tests ( 32 ). In previous studies, pretreatment with an aqueous extract of B. serrata enhances the rats' performances in the Morris water maze and open field tests and corrects memory impairment in LPS-induced inflammation ( 33 ). Similarly, boswellic acids (BAs) and pentacyclic triterpene molecules enhance locomotor performance, reduce inflammatory factors, and increase striatal dopamine levels in rats with rotenone-induced parkinsonism ( 34 ).…”
Section: Discussionmentioning
confidence: 97%